Pola Komunikasi Suami Istri LDR dalam Mengatasi Perselingkuhan di Kota Tanjung Balai - Diva Genefa Andini; Solihah Titin Sumanti (Mahesa Research Center, 2023)
This study aims to understand communication patterns with a pair who are in a long-distance or distant relationship (LDR). To improve family relationships, it is necessary to maintain and pay attention to several things including empathic communication, respect for each party's feelings, the ability to express something, self-discussion, flexibility in behavior, change and new forms of personality that are more compassionate. This study describes communication and marital relationships with long-distance communication that leads to infidelity in conjugal relationships. Case study of a long-distance couple among Indonesian migrant workers living in Tanjung Balai City. The method used to collect and analyze these case studies is qualitative. The method of collecting information is by interviewing and reading reference materials on social media about cheating news on Instagram and partner communication failures. The main cause of frequent communication problems is that couples often engage in one-way communication, which causes a lot of conflict and disagreement, and the inability to adequately resolve existing problems. This communication problem is also exacerbated by the long communication distance, which gives rise to many new problems, and the presence of new people or third parties from the relationship between husband and wife.